Castaway with no soap and a flatulent boffin. - Bullivant, Mike (Times Higher Education Supplement, 2000)
Narrates the author's experience in filming the television series `Rough Science,' with several other British scientists on the island of Capraia in Tuscany, Italy. Concept of the television program; How the scientists were confronted with science-based challenges; How they explored the area's natural resources.